Análisis de una instalación tras 20 años de legionelosis. ¿Qué hemos aprendido? - González-Camacho, Fernando; González-Rubio, Juana María; Cancino-Muñoz, Irving; Coscollá, Mireia (Revista de Salud Ambiental, 2024)
No disponible.